Pengaruh Pemberian Bokashi Jerami Padi dan Kompos Tandan Kelapa Sawit terhadap Perubahan pH, N, P, dan K Tanah Podsolik - Misna Misna; Fadly Hairannoor Yusran; Meldia Septiana (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2022)
Podsolic soil is acidic soil, low nutrient content, especially N, P, K, Ca, Mg. One of the efforts that can be done to overcome this problem in soil is the addition of organic material. The addition of organic material bokashi rice straw and oil palm empty fruit bunches (TKKS) compost can add nutrients in the soil such as nutrients N, P and K. This study aims to determine the effect of rice straw bokashi and oil palm empty compost applied to Podsolic soils. The method used in this study was a single Randomized Complete Design (RAL) with the treatment of dose of 0 t ha-1 (bokashi and TKKS) 3 t ha-1, 5 t ha-1, 7 t ha-1 (bokashi) and 1.5 t ha-1, 3 t ha-1, 4.5 t ha-1 (TKKS). The results of this study indicate that the application of rice straw bokashi and TKKS compost has a significant effect on N-ammonium and P-available.